Drying performance of piper nigrum in a swirling fluidized bed dryer: An experimental study - Nur Fatihah, Mohd Roslan; Ahmmad Shukrie, Md Yudin; Muhammad Afiq, Sumono; Muhammad Faris, Mohamad Pozi; Muhammad Aidil Safuan, Othaman (Penerbit Akademia Baru, 2022)
Sun drying is widely used in drying agricultural products such as piper nigrum because of its ability to dry a high volume in one batch. However, this conventional method of drying has many disadvantages, especially on the hygienic issue. This study investigates the drying performance of piper nigrum by using conventional sun drying and a new dryer called Swirling Fluidized Bed Dryer. Swirling fluidized bed dryer is operated using two inclination angles of air distributors, namely 45°, 67° and one perforated plate distributor. The drying performance is accessed in terms of drying time and moisture content reduction at three different operating temperatures. The results show that the drying time of piper nigrum using a swirling fluidized bed dryer is reduced as compared to conventional sun drying. Besides, the drying performance between different distributors in swirling fluidized bed shows that the moisture content reduction of piper nigrum using 45° angle of air distributor shows the most reduction compared to 67° angle distributor and followed by the perforated distributor. In conclusion, results show that the drying of piper nigrum in a swirling fluidized bed operated with 45° inclination angle of the distributor at high operating temperature gives the best performance.